ANALISIS NILAI RELIGI DALAM GEGURITAN MANIGUNA - Gek Diah Desi Sentana; I Wayan Dharma Suniarmika; Ni Ketut Ayu Nadia Sari (Universitas Hindu Negeri I Gusti Bagus Sugriwa Denpasar, 2021)
The existence of Balinese literary works until now still has a place in the hearts ofBalinese literary lovers, so that the existence of Balinese literary works has lived along withthe times. There are many ways a writer can express his thoughts and ideas, one of which is bywriting a literary work in the form of a geguritan. Balinese purwa (classical) literary worksneed to be preserved, nurtured and developed, because they contain noble values which arevery important, meaning for the life of the people, especially the Balinese. The value theoryfrom Yudibrata is used to reveal the importance of Geguritan Maniguna as a classic literaturethat records culture from a long period of time and contains various cultural paintings, ideas,ethics, advice, entertainment and including religious life, especially regarding religious valuesthat exist. inside it.